2019
DOI: 10.34172/jcvtr.2020.04
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between Framingham, IraPEN and non-laboratory WHO-EMR risk score calculators for cardiovascular risk prediction in a large Iranian population

Abstract: Introduction: Estimation of the risk of cardiovascular diseases (CVD), may lead to prophylactic therapies. This study aims to compare and evaluate the agreement between CVD prediction of Iran Package of Essential Non-communicable Disease (IraPEN) and Framingham risk score (FRS).<br /> Methods: All 40-79 years old participants in the Yazd Health Study who did not have a history of CVD were included. The 10-years risk of CVD was estimated by the laboratory (IraPEN), non-laboratory WHO-EMR B and FRS. The ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…In our study, the FRS classified more people as high risk while the WHO/ISH risk estimator classified more people as low risk. Similar outcomes were seen in studies conducted in Iran and other Asian populations with significant underestimation of 10-year risk by the WHO/ISH score and overestimation of risk by the FRS [36] , [37] , [38] . The risk scores assessed were derived based on different but mostly Western data with only the PCE having a relatively higher proportion of blacks [5] .…”
Section: Discussionsupporting
confidence: 83%
“…In our study, the FRS classified more people as high risk while the WHO/ISH risk estimator classified more people as low risk. Similar outcomes were seen in studies conducted in Iran and other Asian populations with significant underestimation of 10-year risk by the WHO/ISH score and overestimation of risk by the FRS [36] , [37] , [38] . The risk scores assessed were derived based on different but mostly Western data with only the PCE having a relatively higher proportion of blacks [5] .…”
Section: Discussionsupporting
confidence: 83%
“…However, that study used the Cox proportional hazards model to determine the risk 23 , while the present study used the points-based risk scoring system. The results of another study in Iran showed that the agreement between the CVDs risk groupings was negligible with different risk prediction models 16 .…”
Section: Discussionmentioning
confidence: 99%
“…In Iran, Bavarsad et al compared Framingham and World health organization/International society of hypertension (WHO/ISH), and SCORE models 15 . Mirzaei et al assessed Framingham and WHO/ISH models 16 . But no study has been done to examine the agreement between laboratory-based and non-laboratory-based Framingham risk scores.…”
Section: Introductionmentioning
confidence: 99%
“…conducted a study in Yazd, Iran and reported that lack of physical activities and unhealthy eating habits were among the most prominent risk factors of CVDs in a healthy society [ 37 ]. They also reported that 26.5% of Iran’s healthy population would be prone to the high risk of CVDs based on the Framingham risk score (FRS) [ 38 ]. The onset age of CVDs is ten years earlier in Iran than in the developed countries [ 39 ].…”
Section: Discussionmentioning
confidence: 99%